Targeted delivery of functionalized PLGA nanoparticles to macrophages by complexation with the yeast Saccharomyces cerevisiae. Issue 3 (28th November 2019) - Kiefer, Ruth; Jurisic, Marijas; Dahlem, Charlotte; Koch, Marcus; Schmitt, Manfred J.; Kiemer, Alexandra K.; Schneider, Marc; Breinig, Frank
Abstract: Nanoparticles (NPs) are able to deliver a variety of substances into eukaryotic cells. However, their usage is often hampered by a lack of specificity, leading to the undesired uptake of NPs by virtually all cell types. In contrast to this, yeast is known to be specifically taken up into immune cells after entering the body. Therefore, we investigated the interaction of biodegradable surface‐modified poly(lactic‐ co ‐glycolic acid) (PLGA) particles with yeast cells to overcome the unspecificity of the particulate carriers. Cells of different Saccharomyces cerevisiae strains were characterized regarding their interaction with PLGA‐NPs under isotonic and hypotonic conditions. The particles were shown to efficiently interact with yeast cells leading to stable NP/yeast‐complexes allowing to associate or even internalize compounds. Notably, applying those complexes to a coculture model of HeLa cells and macrophages, the macrophages were specifically targeted. This novel nano‐in‐micro carrier system suggests itself as a promising tool for the delivery of biologically active agents into phagocytic cells combining specificity and efficiency. Abstract : The otherwise very promising usage of nanoparticles as delivery vehicle is still hampered by their low targeting efficacy. In this study, Kiefer and co‐workers describe a novel nano‐in‐micro carrier system consisting of biodegradable nanoparticles complexed to Saccharomyces cerevisiae cells. The established complexes can be used for specific and efficient delivery of biologically active agents into phagocytic cells.